Urinary tract infection: a cohort of older people with urinary incontinence - Laís Samara de Melo; Flávia Falci Ercole; Danilo Ulisses de Oliveira; Tatiana Saraiva Pinto; Mariana Avendanha Victoriano; Carla Lúcia Goulart Constant Alcoforado
ABSTRACT Objective: To evaluate epidemiological aspects of urinary tract infection in older patients with urinary incontinence living in long-term care institutions in Belo Horizonte. Method: Concurrent cohort held from April 1st to October 1st, 2015. The study was conducted in two long-term care institutions in the city of Belo Horizonte, Minas Gerais, with 84 incontinent older people. Results: Cumulative incidence of urinary tract infection was 19% (95% CI: 7.83-23.19) and the incidence density was 3.6 cases/100 people-month of follow-up period. The variables Bacteriuria and Institution presented statistical association with the occurrence of urinary tract infection. Conclusion: It is observed that the incidence of urinary tract infection in the study was smaller than in other similar international and national studies, however this is an important world health problem for the older population, with impact on mortality of these individuals.